Design and Implementation of MOAT (Moth Attractor Technology): Glue-Tube-Light System with RTC (Real Time Clock) Module - Wicaksana, Yusuf Aji; Prasetyo, Dani; Syachofina, Himmatul Ulya Alfartri; Oktaviani, Eka Larasati; Wulandari, Retno (Universitas Negeri Malang, 2018)
Massive reduction of onion in Kabupaten Probolinggo was caused by Spodoptera exigua attacks. Since 2012, the significant reduction of onion production was up to 19%. One of the farmers group facing the reduction is Sumber Makmur III with total of reduction is up to 61.69%. The culture technique has done by farmers using conventional lamp and net which have many weaknesses from its implementation. Based on this problem, innovative technology MOAT (Moth Attractor Technology) has created as portable moth attractor. It is the innovative solution using lamp, box and glue completed by RTC (Real Time Clock) and having special glue to intensify the effectiveness and efficiency in exterminating the moths. Following methods have done are (1) literature study and observation, (2) designing product, (3) production, (4) device trials, (5) product’s socialization and implementation, and also (6) monitoring and evaluation. The result is MOAT which can effectively attract up to 770 months in a week. It can help the farmers reduce the damage of onion and increase the production up to 11.07 quintal in 180 m2 area. Furthermore, it can also increase the income of onion farmers.